Dependence of thermoluminescence glow curve of alumina ceramic radiation detectors with the heating rate - Anna Luiza Fraga Silveira; A.C.C. Bernacci; I.V. Nishibayaski; A. Santos; H.R. Ferreira; L.C. Meira-Belo (Brazilian Journal of Radiation Sciences)
Anion defective single crystal detectors α-Al2O3 grown by the Czochralski method are widely used for personal and area monitoring. A methodology for the production of polycrystalline ceramic detectors α-Al2O3 based on the sol-gel method was developed in our research group. The dependence of the thermoluminescent response with the heating rate was studied in the range from 0.1 K/s to 10 K/s for both, ceramic produced by our research group and commercial single crystal detectors (TLD-500 like). The studies were performed at a RISØ TL/OSL DA-20 reader - DTU Nutech. All irradiations were done by means of a 90Sr/90Y beta source facility installed at the reader. In order to study the influence of the heating rate on the luminescent response, the ceramic alumina detectors and single crystal alumina detectors were irradiated with an absorbed dose about 12,5 mGy. A comparison between the two types of detectors revealed that the single crystal presented a response five times greater than the response of the ceramic with a linear heating rate of 0.1 K/s. Nevertheless, the response of both of them is almost the same as a heating rate of 7 K/s, which for routine applications is very interesting. It is important to note that while the response of the single crystal decay almost exponentially with the heating rate, which is in accord with specialized literature, the response of the ceramic detector decays almost linearly.